Produção de óleo e material adsorvente a partir da biomassa do fungo Nigrospora sp. - Tonato, Denise (2019)
This works was focused on the production of microbial oil from the biomass of the fungus Nigrospora sp. and the reuse of defated residual biomass as a biosorbent to recovery dye from aqueous solution. The study was divided into three parts. In the first one, it was necessary to study a strategy to maximize the biomass concentration and lipid accumulation of the fungus Nigrospora sp., by investigating different composition and process variables of the media in shaken flasks, and the influence of the stirring rate and aeration in bioreactor, in batch and fed batch modes. The extraction of lipids in this first stage wase carried out by the Soxhlet method. The maximum concentration of biomass and lipid yield obtained was 18.80 g L-1 and 3.94% in shaken flasks and 40.17 g L-1 and 21.32% in the bioreactor, respectively. In the second part of the study, it was investigated three strategies to extract the oil from microbial cells: i) using only supercritical CO2 ; ultrasound treatment followed by supercritical CO2 extraction; co-solvent combined with ultrasound treatment followed by supercritical CO2 extraction. The parameters evaluated were temperature (40-80 °C), pressure (15-25 MPa), pre-treatment time of ultrasound (15-60 min) and addition of ethanol (30-70 g / 100 g of biomass). The highest oil yield was 3.94% with a total fatty acids of 45.5 g/100 g oil, obtained at 80 °C and 25 MPa with 50% by weight ethanol after ultrasound pretreatment of the biomass for 60 min. In the third and final part of the study, the use of the defatted residual biomass (RDB) of the fungus Nigrospora sp., obtained from the process of supercritical extraction of lipids was used as a biosorbent for the removal of the red dye Procion (PR H-E7B) from aqueous solutions. For this, it was necessary to evaluate the influence of different process variables on biosorption from the kinetic and equilibrium points of view. The RDB showed potential as a biosorbent, with a biosorption capacity of 188.79 mg g-1.